Revision of world Ceroptresini (Hymenoptera: Cynipidae) with the description of a new genus and five new species - Lobato-Vila, Irene; Pujade-Villar, Juli (Zootaxa, 2019)
A taxonomic revision of the tribe Ceroptresini (Hymenoptera: Cynipidae) is conducted for the first time. Prior to this study, the total number of valid species of Ceroptres, the only genus within Ceroptresini to date, was 23. As a result of this revision, 15 Ceroptres species are retained as valid and one species, Amblynotus ensiger Walsh, 1864, is desynonymized from Ceroptres petiolicola (Osten-Sacken, 1861), being considered here as a valid Ceroptres species: C. ensiger (Walsh, 1864) status verified and comb. nov. An additional five new species are described from Mexico: Ceroptres junquerasi Lobato-Vila & Pujade-Villar sp. nov.; C. lenis Lobato-Vila & Pujade-Villar sp. nov.; C. mexicanus Lobato-Vila & Pujade-Villar sp. nov.; C. nigricrus Lobato-Vila & Pujade-Villar sp. nov.; C. quadratifacies Lobato-Vila & Pujade-Villar sp. nov., increasing the total number of valid Ceroptres species to 21. Ceroptres masudai Abe, 1997 is synonymized with C. kovalevi Belizin, 1973. Ceroptres niger Fullaway, 1911 is transferred to Andricus (Andricus confusus Lobato-Vila & Pujade-Villar comb. nov. and nom. nov.). Five species (Amblynotus inermis Walsh, 1864; Cynips quercusarbos Fitch, 1859; Cynips querficus Fitch, 1859; Cynips quercuspisum Fitch, 1859; and Cynips quercustuber Fitch, 1859) are not considered as valid Ceroptres. The status of Ceroptres quereicola (Shinji, 1938), previously classified as an unplaced species, is commented on. In addition, a Nearctic species from the USA, Ceroptres politus Ashmead, 1896, is here proposed as the type species of a new genus within Ceroptresini: Buffingtonella Lobato-Vila & Pujade-Villar gen. nov. Redescriptions, biological and distribution data, illustrations and keys to genera and species within Ceroptresini are provided. The diagnostic morphological traits of Ceroptresini, Ceroptres and the new genus are discussed.